DAMPAK SOSIAL KEGIATAN PABRIK KARET PT. P&P BANGKINANG DI KELURAHAN WONOREJO KECAMATAN MARPOYAN DAMAI KOTA PEKANBARU - Ligaya Safitri; Nurhamlin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Industry influence physical consequences in societ. Consequences felt by the community withthe industry could be in many different forms. The problem addressed in this paper is todescribe the social impact of the rubber factory activity. The goal is to find out what theimpact of the rubber plant and to find out how the adaptation of the strategy against thenegative impact of rubber factory. The population of this study is that people who live in theDistrict Marpoyan RW.02/RT.04 Peace Village Wonorejo Pekanbaru city, amounting to 105families ( head of household ), the sampling technique with random samples taken as much as50 % as many as 53 families. The method used is descriptive quantitative methods withquantitative data analysis. The research instrument used was a questionnaire, interview anddocumentation. The theory used for this problem is that the theory of Paul BellEnvironmental Perception Theory. The results of the study in general, the writer can say thatthe positive impact absorbing rubber factory workers around 18.9 % of the public and thepublic has an opportunity to strive 18.8 %. Of employment and business opportunities iscontributing to people's income. The negative impact of rubber factory pollutes the air likethe smell of decaying society interfere with 79.2 % of respondents highly annoyed by airpollution, generate noise and traffic congestion. Community adaptation strategies to face thenegative impacts such as odor 76.8 % of respondents overcome by installing freshener inevery room.Keywords : social impacts, adaptation strategies, rubber plant